Voice of the Hungry nation : (Asian human right commission, 1999)
This book reports evidence, findings and conclusions of the People's Tribunal on Food Scarcity and Militarization in Burma. Concerned by reports of widespread hunger due to military rule in Burma (Myanmar), in 1997 AHRC began preparing for The People's Tribunal. The Tribunal was created to investigate and expose human rights violations in a nation where legal recourse does not exist. Its purpose was to highlight militarization's devastating effects on Burma's silent, often forgotten rural population. Sitting on the Tribunal were three prominent members of Asia's human rights movement: Justice H. Suresh (India), Professor Mark Tamthai (Thailand) and Dr. Lao Mong Hay (Cambodia)). Throughout 1999 this panel reviewed evidence, took depositions, and deliberated its findings and recommendations.